2020
DOI: 10.3390/polym12061298
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Newly Isolated Bacterium Aneurinibacillus sp. H1 as an Auspicious Thermophilic Producer of Various Polyhydroxyalkanoates (PHA) Copolymers–2. Material Study on the Produced Copolymers

Abstract: Aneurinibacillus sp. H1 is a promising, moderately thermophilic, novel Gram-positive bacterium capable of the biosynthesis of polyhydroxyalkanoates (PHA) with tunable monomer composition. In particular, the strain is able to synthesize copolymers of 3-hydroxybutyrate (3HB), 4-hydroxybutyrate (4HB) and 3-hydroxyvalerate (3HV) with remarkably high 4HB and 3HV fractions. In this study we performed an in-depth material analysis of PHA polymers produced by Aneurinibacillus sp. H1 in order to describe how the monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…The ratio between P3HB and P4HB crystallites gradually shifted with changing copolymer composition, confirming the copolymer composition found by the GC-FID method. The diffraction patterns correspond well with previously described data [ 12 ] obtained on materials produced by the same microorganism as in this work. Other authors (see Ref.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The ratio between P3HB and P4HB crystallites gradually shifted with changing copolymer composition, confirming the copolymer composition found by the GC-FID method. The diffraction patterns correspond well with previously described data [ 12 ] obtained on materials produced by the same microorganism as in this work. Other authors (see Ref.…”
Section: Resultssupporting
confidence: 90%
“…H1 reaches lower cell dry mass/biomass yields, and the obtained biomass is quite poor in PHA content as compared to C. necator (see Table 1 ). Furthermore, produced copolymers dispose of a significantly lower average molecular weight than homopolymers, which is given by the difference in PHA synthase types of the respective producents and their general biological dissimilarity (as proposed in [ 12 ]), and possible polymerization termination by glycerol [ 13 , 14 ]. On the other hand, manipulating the monomer composition is expected to broaden the range of accessible physical and material properties (crystallinity, ultimate tensile strength), resulting in higher applicability.…”
Section: Resultsmentioning
confidence: 99%
“…However, when supplemented with 1,4-butanediol, the strain produced P(3HB- co -4HB) with 4HB molar fraction up to 90 mol%. Moreover, by cofeeding valerate, it was able to synthesize terpolymer P(3HB- co -33 mol% 3HV- co -54 mol% 4HB) [ 25 ].…”
Section: Microbial Synthesis Of P4hbmentioning
confidence: 99%
“…Recently, it was reported that Aneurinibacillus sp. H1 has potential for the biosynthesis of polyhydroxyalkanoates (PHA) on an industrial scale, and its capacity for production of copolymers such as 3-hydroxybutyrate (3HB), 4-hydroxybutyrate (4HB), and 3-hydroxyvalerate (3HV) with exceptionally high 4HB and 3HV fractions [22]. Furthermore, A. aneurinilyticus DBT87 isolated from the swine and goat can produce cellulase and xylanase enzymes, which can degrade lignocellulose biomass [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, only a limited number of genomes were used in such studies. This limits our understanding of the complete potential of microorganisms, which have shown great capabilities for diverse types of enzyme activities, or the production of bioactive compounds [16,22,[37][38][39][40]. Therefore, in this work we apply genome mining approaches to investigate the biosynthetic potential as well as explore the diverse sets of enzymes for biomass degradation and heavy metal resistance present in Aneurinibacillus genomes.…”
Section: Introductionmentioning
confidence: 99%